Cardioprotective effect of dipeptidyl peptidase-4 inhibitor during ischemia-reperfusion injury - Kroekkiat Chinda (2018)
Background: Dipeptidyl peptidase-4 (DPP-4) inhibitor is a new anti-diabetic drug for type-2 diabetes mellitus patients. Despite its benefits on glycemic control, the effects of DPP-4 inhibitor on the heart during ischemia-reperfusion (I/R) periods are not known. We investigated the effect of DPP-4 inhibitor on cardiac electrophysiology and infarct size in a clinically relevant I/R model in swine and its underlying cardioprotective mechanism. Methods: Fourteen pigs were randomized to receive either DPP-4 inhibitor (vildagliptin) 50 mg or normal saline intravenously prior to a 90-min left anterior descending artery occlusion, followed by a 120-min reperfusion period. The hemodynamic, cardiac electrophysiological and arrhythmic parameters, and the infarct size were determined before and during I/R. Rat cardiac mitochondria were used to study the protective effects of DPP-4 inhibitor on cardiac mitochondrial dysfunction caused by severe oxidative stress induced by H2O2to mimic the I/R condition. Results: Compared to the saline group, DPP-4 inhibitor attenuated the shortening of the effective refractory period (ERP), decreased the number of PVCs, increased the ventricular fibrillation threshold (VFT) during the ischemic period, and also decreased the infarct size. In cardiac mitochondria, DPP-4 inhibitor decreased the reactive oxygen species (ROS) production and prevented cardiac mitochondrial depolarization caused by severe oxidative stress. Conclusions: During I/R, DPP-4 inhibitor stabilized the cardiac electrophysiology by preventing the ERP shortening, decreasing the number of PVCs, increasing the VFT, and decreasing the infarct size. This cardioprotective effect could be due to its prevention of cardiac mitochondrial dysfunction caused by severe oxidative stress during I/R. © 2013 Elsevier Ireland Ltd. All rights reserved.